Dysphagia and Odynophagia in a Cardiac Transplant Patient: A Case of Mycophenolic Acid–Induced Esophagitis and Esophageal Stricture. Issue 4 (14th April 2022) - Schell, Trevor L.; Lindholm, Christopher R.; Grimes, Ian
ABSTRACT: Mycophenolic acid (MPA) is associated with many gastrointestinal (GI) side effects that vary in severity and location. Upper GI effects have previously been attributed to topical mucosal irritation similar to nonsteroidal anti-inflammatory drug pathology. We describe a case of severe MPA-induced esophagitis complicated by esophageal stricture in a patient receiving multiple formulations of MPA, including oral enteric-coated mycophenolate sodium and mycophenolate mofetil administered both intravenous and by J-tube. Endoscopy revealed complete resolution of esophagitis following discontinuation of all MPA formulations, demonstrating that upper GI toxicity may occur because of local and systemic effects.